INTER-RELATIONSHIP OF LIVER AS A PART OF HAYAT AL AZA (MORPHOLOGY) IN THE FORMATION OF TEMPERAMENT IN UNANI SYSTEM OF MEDICINE (International Journal of Ayurveda and Pharma Research, 2020)
Temperament occupies an important place in Unani Medicine and forms the basis of pathology, diagnosis and treatment. This concept was originally introduced by Hippocrates (460-370 BC) in which he stated that “It is more important to know what sort of person has a disease than to know what sort of disease a person has”. Ibn Sina says “Allah most beneficent has furnished every one and each of its member with a temperament which is entirely the most appropriate and best adopted for the performance of its functions and passive state”. Human interest in the liver is as old as the science of medicine. Since time immemorial it has been considered as one of the vital organs of a human body. It was during the Greco-Arabian period of medical history that the intimate relationship between the liver and the health of the individual was established. Considering liver as an important and essential organ, Hippocrates (460-377 BC) says “if we live a good life, it is because of the health of our liver” (Ibn-e-Zohr, 1989). Galen (131-210AD) believed that liver retained a dominant role as the “seat of sanguification and the source of veins”. According to Avicenna- “Physicians regard the liver as the seat of manufacture of the dense part of the humours” (Grunner, 1930). Avicenna further writes- “Liver is a large factory where due to digestive and metabolic changes, the various humours of the body are formed in plenty (Kabiruddin, 1947). According to Unani Physicians, humours play an important and deciding role in the creation of human temperament. Therefore it can be revealed that liver is an important metabolic organ, which plays an important role in the formation of temperament of a person.